If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x^2+3*x)/(3*x^2+2)
a^5*((10*a^3)/y)*y*((3*y^3)/4) = 0
x/2 = 3-(x/4)
(x-1)/7-((x-3)/2) = 1
3;7;4;9;0;0
| 8z+1-z=6+6z+6 | | 4*x=x | | Y=x^3+c^2-12x | | hbt=2(3.14) | | 0.75x=92 | | 3y=19x+86 | | (3y^3/4a^5y)*(10a^3/y) | | (n+6)(n-6)=5n | | 7+6x=5+3x | | -6=-5x+x^2 | | 11(v+4)-3v=4(2v+3)-17 | | 27d^6+8g^12=0 | | 3+2w=19 | | (x)=-2x^2+7x-4 | | 2lnx+4=5+lnx | | wx^2-w^2x^2=0 | | F(x)=5x^2+10x+12 | | 6t+8=26-3t | | 6y-1=8y-3y | | x/2=3-x/4 | | 8x^3-12x^2-10x+15= | | (x-1)/7-(x-3)/2=1 | | X=4x^2-9x+2 | | 4a+6=36 | | (x)=-2x^2+9x+5 | | x-.03x=158.92 | | 2g+6=6g-6 | | H(x)=-2x^2+9x+5 | | F(x)=4cos^2-6sin^2x | | x-3y=y+2x | | 4z-1=7z+4z | | (2x+16)=(4x-4) |